2019
DOI: 10.3390/ijerph16071277
|View full text |Cite
|
Sign up to set email alerts
|

A Land Use/Land Cover Based Green Development Study for Different Functional Regions in the Jiangsu Province, China

Abstract: Land use/land cover (LULC) change can strongly affect carbon storage in terrestrial ecosystems. The rapid development of China’s economy has formed different functional regions. These functional regions profoundly affect land use patterns. Thus, assessing the carbon storage induced by LULC changes is significant for green development. Selecting the typical region of the Jiangsu Province as the study area, this study first examines the research associated with the regional functional characteristics and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…With acceleration of urbanization of land, China’s structure, intensity, and efficiency of land use have changed. Feng and Guo et al studied LUCC and carbon emissions of cities and showed that the increase in construction land and the decrease in vegetation cover led to a significant decline in carbon storage [ 35 , 36 ]. Zhang et al confirmed that there was a two-way causal relationship between the quality of land urbanization and carbon emissions, and the former had a negative impact on carbon emissions in various provinces [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With acceleration of urbanization of land, China’s structure, intensity, and efficiency of land use have changed. Feng and Guo et al studied LUCC and carbon emissions of cities and showed that the increase in construction land and the decrease in vegetation cover led to a significant decline in carbon storage [ 35 , 36 ]. Zhang et al confirmed that there was a two-way causal relationship between the quality of land urbanization and carbon emissions, and the former had a negative impact on carbon emissions in various provinces [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different methods have been used to measure and analyze the efficiency of UILU, such as indicator systems [11,12], data envelope analysis (DEA) [4,[13][14][15], and the directional distance function model [16,17]. Many researchers have also attempted to measure and evaluate the intensification of UILU, mainly using comprehensive indicator systems [18][19][20][21][22]. As a result, many proposals to improve efficiency and promote intensification have been made.…”
Section: Introductionmentioning
confidence: 99%